No Fault Compensation for Medical Injuries - Flis, Vojko (Medicine, Law & Society, 2016)
For decades in both Europe and the United states , the issue of compensation for victims f medical injuries has led to lively debates. Many scholars have analyzed the adverse effects of the „tort system” (based on negligence standards and court proceedings) on the increasing costs of insurance premiums, on the patient-doctor relationship and the quality of care. These debates have led to changes in compensation in some countries. Compensation would be based not on negligence, but rather on a broader avoidable medical injury standard. Some nations have long operated administrative schemes based on no fault principle. No fault compensaton model for victims of medical injuries might be characterized by the choices it makes regarding some key issues: (a) the definiton of compensation criteria in particular the status given to fault; (b) the organization of the decision -making process. What type of body adjudicates medical claims? (c) Who finances the mechanism. What injuries are likely to be compensated for, to what extent and by whom? This article reviews the origins and operations of the no fault systems, the evolution of their compensation criteria, and how these criteria are actually applied.